2016
DOI: 10.4172/2161-1165.1000237
|View full text |Cite
|
Sign up to set email alerts
|

Malaria among the Geriatric Population in Parts of South-Eastern Nigeria: Prevalence, Complications and Co-morbidity with Non-communicable Diseases

Abstract: This study was done to ascertain malaria prevalence, its complications and co-morbidity with non communicable diseases among the geriatric population in parts of South-Eastern, Nigeria. Ninety two (92) consenting subjects between the ages of 50 and 80 years were recruited in Ihiagwa, South-Eastern Nigeria for the study. Blood samples collected from them were Giemsa stained and examined microscopically for malaria parasites. Clinical examination in addition to health facility records analysis were done to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 16 publications
0
14
4
Order By: Relevance
“…It is possible that, unlike immunity to other infectious diseases, malaria immunity – the mechanisms of which are not yet fully elucidated – is not significantly impacted by comorbidity among people living in malarial endemic zones such as Nigeria. This finding is however contrary to the reports by Chukwuocha et al 15 and Ibrahim et al 30 who, respectively, demonstrated statistical association between malaria infection and certain NCDs. Also, studies in non-endemic regions among patients, who returned from endemic areas, showed significant association between NCDs and the risk of malaria infection as well as its severity.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…It is possible that, unlike immunity to other infectious diseases, malaria immunity – the mechanisms of which are not yet fully elucidated – is not significantly impacted by comorbidity among people living in malarial endemic zones such as Nigeria. This finding is however contrary to the reports by Chukwuocha et al 15 and Ibrahim et al 30 who, respectively, demonstrated statistical association between malaria infection and certain NCDs. Also, studies in non-endemic regions among patients, who returned from endemic areas, showed significant association between NCDs and the risk of malaria infection as well as its severity.…”
Section: Discussioncontrasting
confidence: 94%
“… 3 , 14 , 15 This prevalence was lower to that obtained in other studies in Southwest and Southeast Nigeria probably due to variations in study population structure and timing of survey. 14 , 15 …”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations